The cuckoo bird - Corbalis, Judy.; Armitage, David, 1943- ([New York, NY] : HarperCollins, 1991)
A little girl and her grandmother try to outwit a shape-changing, greedy cuckoo bird who has tricked his way into their house.
Booklist
School Library Journal
Kirkus Reviews
4.5
K-3
Keywords: Cuckoos -- Fiction; Behavior -- Fiction; Cuckoos -- Fiction